MALARIA IN CHILDREN - Richard-Fabian Schumacher; Elena Spinelli (Mediterranean Journal of Hematology and Infectious Diseases)
This review is focused on childhood specific aspects of malaria, especially in resource-poor settings. We summarise the actual knowledge in the field of epidemiology, clinical presentation, diagnosis, management and prevention.